Spatial Analysis Of Hypertension Incidence In The Area Tuntungan Community Health Center In 2023 - Diwanta, Faradilla; Nanda, Meutia; Astuty, Delfriana Ayu; Wahyuni, Raduwi; Adelia, Difa; Zahrani, Windi (Tadulako University, 2025)
Hypertension is a non-communicable disease (NCD) known as a silent killer because it often shows no symptoms but can cause serious complications and even death. In Indonesia, the prevalence of hypertension continues to increase, even exceeding the global average. This study aims to analyze the spatial distribution of hypertension cases and their characteristics based on gender in the working area of the Tuntungan Community Health Center (UPT Puskesmas Tuntungan) in 2023. The research design used was an ecological study with a spatial analysis approach. Secondary data were obtained from records of hypertension cases based on villages in the working area of the Tuntungan Community Health Center. The analysis was performed descriptively using QGIS and GeoDa software to produce spatial distribution maps and incidence rates (IR). The data were also analyzed based on the characteristics of the patients' gender. The results showed that the total number of hypertension cases in 2023 was 14,452, with a slightly higher proportion of women (51.15%) than men (48.85%). Spatial distribution showed the highest concentration of cases in several villages, such as Salam Tani, Namorih, Tiang Layar, Namo Simpur, and Tengah. The village of Salam Tani recorded the highest percentage of cases at 8.3%. Based on incidence analysis, the villages with the highest IR were Salam Tani, Durin Simbelang, Namo Riam, Durin Tonggal, and Lama, with an IR of 99.2 per 1,000 population. Unhealthy lifestyles, low physical activity, and low socioeconomic status were the main determinants of the high prevalence of hypertension. In addition, there are differences in the distribution of cases based on gender, which indicates the need for an intervention approach that considers gender aspects. These findings indicate that spatial analysis can be an important tool in identifying priority areas for promotional and preventive interventions. Effective hypertension control strategies need to be tailored to the demographic, geographic, and social characteristics of the local community.